Material Acts in Everyday Hindu Worlds - Flueckiger, Joyce Burkhalter (State University of New York Press, 2023)
In Material Acts in Everyday Hindu Worlds, Joyce Burkhalter Flueckiger analyzes the agency of materiality—the ability of materials to have an effect on both humans and deities—beyond human intentions. Using materials from three regions where Flueckiger conducted extensive fieldwork, she begins with Indian understandings of the agency of ornaments that have the desired effects of protecting women and making them more auspicious. Subsequent chapters bring in examples of materiality that are agentive beyond human intentions, from a south Indian goddess tradition where female guising transforms the aggressive masculinity of men who wear saris, braids, and breasts to the presence of cement images of Ravana in Chhattisgarh, which perform alternative theologies and ideologies to those of dominant textual traditions of the Ramayana epic. Deeply ethnographic and accessibly written, Material Acts in Everyday Hindu Worlds expands our understanding of material agency as well as the parameters of religion more broadly.This book is freely available in an open access edition thanks to the National Endowment for the Humanities Fellowships Open Book Program—a limited competition designed to make outstanding humanities books available to a wide audience. Learn more at the Fellowships Open Book Program at https://www.neh.gov/grants/odh/FOBP, and access the book online at the SUNY Open Access Repository at https://soar.suny.edu/handle/20.500.12648/8716.